THE EFFECT OF SPACING PLANT AND WEEDS AS ORGANIC MULCH ON THE GROWTH AND RESULTS OF SWEET CORN (ZEA MAYS SACCHARATA STURT) - Yenni Asbur; Yayuk Purwaningrum; Murni Sari Rahayu; Bambang Nurdiansyah (Journal of Islamic, Social, Economics and Development, 2023)
Sweet corn (Zea mays saccharate Stuart) is the most popular plant in Indonesia at the moment because it tastes sweet and can be processed into various kinds of food, from corn, grilled, corn on the cob, corn fritters, corn cakes and also as a mixture of salads and preparations. other vegetables. However, the ever-increasing demand for sweet corn has not been matched by an ever-increasing yield. The purpose of this study was to determine the optimum plant spacing and the best type of mulch for the growth and yield of sweet corn. The research was conducted in the experimental field of the Faculty of Agriculture, Universitas Islam Sumatera Utara, Gedung Johor, Medan (3°31'23" N 98°39'51" E) with a flat topography and an altitude of ± 25 masl. The study was designed using a two-factor randomized block design. The first factor is the spacing (S), namely 25 cm x 50 cm (S1), 25 cm x 75 cm (S2), and 25 cm x 100 cm (S3). The second factor was the type of weeds used as organic mulch (M), namely A. gangetica (M1), N. biserrata (M2), and P. conjugatum (M3). The dose of mulch used was 5 tons/ha and all treatments were repeated three times. The results showed that the optimum spacing for the best growth of sweet corn was 25 cm x 75 cm and 25 cm x 100 cm and the best organic mulch for the growth and yield of sweet corn was P. conjugatum and A. gangetica